Synthesis and Characterization of Some C2-Symmetric Copper(II), Ruthenium(II) and Chromium(0) Complexes with Quadridentate Ligands having 2-Quinolinyl Auxiliary Groups - S. Abu-Surrah, Adnan (Asian Journal of Chemistry, 2012)
Some new octahedral transition metal carbonyl and dichloro complexes (2-7) of the tetrapodal, stereorigid amine ligands (N,N’-dibenzyl-N,N’-di(quinoline-2-methyl)-1,2-ethylenediamine (DBQED) (1a) and N,N’-dimethyl-N,N’-di(quinoline-2-methyl)-1,2-ethylene diamine (DMQED) (1b) have been prepared and characterized. The reaction of the ligands with CuCl2.2H2O afforded the corresponding Cu(II) dichloride complexes [(DBQED)CuCl2] (2) and [(DMQED)CuCl2] (3), respectively. Ru(II) complexes of the types [(DBQED)RuCl2] (4) and [(DBQED) Ru (CO)2Cl2] (5) were prepared by the treatment of RuCl3.3H2O or Ru (CO)2Cl2]n with the ligand DBQED. The chromium(0) carbonyl complexes [(DMQED )Cr(CO)2 ] (6) and [(DBQED)Cr(CO)4] (7) were prepared by refluxing the corresponding ligand with Cr(CO)6 in xylene. In the complexes (2, 3, 4 and 6) the ligands act as a tetradentate chelate. While in 1 and 7 the ligand coordinates in a bidentate fashion.